Climate change, food security, and diarrhoea prevalence nexus in Tanzania - Kitole, Felician A.; Mbukwa, Justine N.; Tibamanya, Felister Y.; Sesabo, Jennifer K. (humanities and social sciences communications, 2024)
Article published by Palgrave in the Journal of Humanities and Social Sciences Communications Volume 11, Issue 1, Pages 1-13